Mussel oil is superior to fish oil in preventing atherosclerosis of ApoE−/− mice - Li, Kelei; Song, Xiaolei; Li, Huiying; Kuang, Xiaotong; Liu, Shiyi; Liu, Run; Li, Duo (Frontiers in Nutrition, 2024)
Objectives: The present study aimed to explore the preventive effect of mussel oil (MO) on atherosclerosis and the potential mechanism in apolipoprotein E-null (ApoE -/-) mice.Methods: ApoE -/-mice were fed with a high-fat and high-cholesterol chow, and given corn oil (CO), fish oil (FO), MO or aspirin (ASP, dissolved in CO) by gavage for 12 weeks. The total n-3 polyunsaturated fatty acids (PUFA) in MO (51.01%) and FO (46.82%) was comparable (mainly C22:6n-3 and C20:5n-3). Wild-type mice were fed with a normal chow and given equivalent CO as health control (CON).Results: Compared with CON group, obvious atherosclerotic plaque appeared at aorta and aortic sinus in CO group. Compared with CO group, MO but not FO had a significantly smaller atherosclerotic plaque area in aorta. The aortic atherosclerotic plaque area was comparable in MO, CON and ASP groups. MO group had a significantly smaller atherosclerotic plaque area, lower lipid deposition, lower contents of smooth muscle cell (SMC) and slightly lower contents of macrophage at aortic sinus than FO group. Serum concentrations of IL-1β, NF-κB and VCAM-1 were comparable in MO and FO groups, and were significantly lower than CO group. Compared with CO group, MO group but not FO group had a significantly lower aortic protein levels of p65NF-κB, p38MAPK and VCAM-1. The aortic protein levels of p-p65NF-κB and p-p38MAPK were significantly lower in MO group than FO group.In conclusion, MO is more potent than FO in preventing atherosclerosis, and the possible mechanism may be by downregulating p38MAPK/NF-κB signaling pathway, decreasing VCAM-1 and macrophage, and inhibiting proliferation and migration of SMC.